Interdependence Practice among Elderly People with Severe Cataract Blindness in Malaysia - Abdul Mutalib, Othman; Asma', Hassan; Nurulain, Mat Zin; Ahmad Shahir, Abdul Mutalib (2017)
The practice of interdependence are essential among the Malay older people in the community to sustain healthy daily living activities and enhanced quality of life (QoL) (Abdul Mutalib et al, 2016). Contributing factors include family support, personal beliefs, cultural affiliations, and religious obligations. The benefits include reducing depression and social isolation, and significant improvement in their health status, socialisation and life satisfaction (Abdul Mutalib et al, 2016; Wan-Ibrahim & Zainab, 2014). However, the second National Eye Survey (NES II) 2014 revealed the prevalence of blindness and low vision among the older people aged 50 and above in the country as 1.2 % and 5.4 % respectively (Mohamad Aziz Salowi, 2014). The single main cause of blindness and low vision was cataract with estimated number of eyes that require surgery in 2014 was more than 670 000. Majority of the patients with cataract believed they did not need surgical treatment (Mohamad Aziz Salowi, 2014). They seems to have limited awareness that individuals facing vision loss are at higher risk of falls, injuries, depression and social isolation, and the heightened effects of other health conditions (Stuck et. al., 1999). The aim of this study is to understand how the elderly people in Malaysia could endure their progressive visual deterioration until blindness due to cataract in spite of active interdependence practice. It will enable health practitioners to find ways to effectively advocate and promote earlier cataract surgical treatment to improve their QoL.